RESEARCH OF INFLUENCE OF BURNING MODES FOR INTERMEDIATE PRODUCT OF MAGNESIA REFRACTORIES ON PHYSICAL AND CERAMIC FACTORS OF THE FINISHED PRODUCTS - Kulikov , Yuri; Varchenko , Dmitri; Karpenko , Ann (Scientific Journal "Metallurgy", 2020)
Investigations were made of the firing temperature and the duration of holding during pressing at the maximum value on the physico-ceramic properties of the calcined magnesia refractories obtained on the basis of fused perclase with a low content of oxide impurities. Improving the quality of magnesia refractories begins with an increase in the content of magnesium oxide, an increase in the size of periclase crystals and the density of cross-linking powders. Fused perclase is widely used in the preparation of products, powders and thermal insulation. Not taking into account the energy costs of smelting, the use of fused periclases in some cases is economically beneficial by increasing the service life of such materials. The paper presents experimental studies of the influence of the firing regimes of semi-finished products on the physical and ceramic properties of the resulting product. In the sintering process, the following internal processes occur: a change in the size and shape of pores, an increase in crystals, a decrease in residual stress, the formation of a liquid phase, phase redistribution, and a decrease in the concentration of defects in crystalline phases. The paper presents a chemical analysis of fused crosslink powders. Investigations of refractory firing modes have been carried out. Samples made of fused cross-section pressed under the influence of pressure of 98 kPa were annealed. The firing was carried out at temperatures from 1800 to 2000 K and isothermal holding for 5 hours. As an analysis of the results showed, an increase in the firing temperature from 1833 to 1973 K reduces the porosity of the refractory from 16.8% to 12.3%. The structure of such a material has an inhomogeneous fragmentation structure due to the content of significant aggregate grains and fused crossover single crystals, along with an insufficiently sintered binder mass of the same composition. For samples obtained at 1973 K, a more dense crystalline structure is characteristic due to the tight contact between the filler grains and the binder. The silicate phases in the microstructure of the samples are located in thin layers between MgO grains.To increase the yield of products, it is necessary to adhere to a minimum deformation of products during firing.